STRATEGI KOMUNIKASI HUMAS KEMHAN RI DALAM MEMBANGUN CITRA POSITIF MELALUI MEDIA SOSIAL - Shafa Arawinda (2022)
The Indonesian Ministry of Defense (Kemhan RI) is highly valued by the public in terms of protecting the Indonesian state from various non-traditional threats such as terrorism. Strategically triggered by ideology, politics, economy and society, socio-culture, as well as security situations and conditions, when an incident involving the defense of the Indonesian state is the background, of course there will be positive and negative news. Monitoring the news about the Ministry of Defense of the Republic of Indonesia and planning and implementing strategies to deal with the news circulating in the media is a public relations task This study aims to discuss public relations communication strategies and obstacles in building a positive image through social media of the Indonesian Ministry of Defense using impression management theory. This study uses a qualitative research method with a case study approach. The data collection technique was done by purposive sampling. Researchers used four stages of data analysis, namely data collection, data reduction, data presentation, and withdrawal/verification by data triangulation. There are 2 key informants in this study and 2 informants, namely people who were selected based on criteria that have been determined by the author, namely the Public Relations of the Indonesian Ministry of Defense, the Opinion section. This research uses impression management theory. The results of this study are the Public Relations of the Ministry of Defense of the Republic of Indonesia in building a positive image through social media, namely (1) seeing the dynamics that develop and carrying out information thickening; (2) create content that is liked by the community with an attractive and light design; (3) planning content by monitoring through media analysis; (4) accept criticism on social media and respond comprehensively; (5) publish through social media and collaborate with other ministries and influencers; (6) holding seminars and quizzes to interact with the community; (7) carry out planning, implementation and evaluation strategies.